2019
DOI: 10.1128/mcb.00285-18
|View full text |Cite
|
Sign up to set email alerts
|

DDX3 Participates in Translational Control of Inflammation Induced by Infections and Injuries

Abstract: Recent studies have suggested that DDX3 functions in antiviral innate immunity, but the underlying mechanism remains elusive. We previously identified target mRNAs whose translation is controlled by DDX3. Pathway enrichment analysis of these targets indicated that DDX3 is involved in various infections and inflammation. Using immunoblotting, we confirmed that PACT, STAT1, GNB2, Rac1, TAK1, and p38 mitogen-activated protein kinase (MAPK) proteins are downregulated by DDX3 knockdown in human monocytic THP-1 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 75 publications
(118 reference statements)
4
27
0
Order By: Relevance
“…This indicates that Belle interacts predominantly with mature mRNAs and preferentially acts as a translational regulator. In accordance with previously published data, Belle/DDX3 can be involved both in translational repression and translational activation of target transcripts [18,[26][27][28][73][74][75][76]. Our CLIP-seq analysis provides entry points in attempting to understand the molecular mechanisms underlying the spermatogenesis defects observed in both in somatic cyst cells and in the germline with failures of Belle expression.…”
Section: Discussionsupporting
confidence: 87%
“…This indicates that Belle interacts predominantly with mature mRNAs and preferentially acts as a translational regulator. In accordance with previously published data, Belle/DDX3 can be involved both in translational repression and translational activation of target transcripts [18,[26][27][28][73][74][75][76]. Our CLIP-seq analysis provides entry points in attempting to understand the molecular mechanisms underlying the spermatogenesis defects observed in both in somatic cyst cells and in the germline with failures of Belle expression.…”
Section: Discussionsupporting
confidence: 87%
“…The direct role of DDX3 in regulating pro-inflammatory responses in the pathogenesis of bowel disease and Listeria infection were also recently observed (62,63). Inhibition of DDX3 activity stalled the translation of target proteins (38,64), resulting in a decrease of cytokine secretion and inhibition of macrophage migration and phagocytosis (38). It therefore appears plausible that DDX3-dependent translational control may be the mechanism that regulates microglial activation in neuroinflammatory pathways.…”
Section: Discussionmentioning
confidence: 92%
“…These pathways are well known to control the inflammatory response, cytokine secretion, and migration of macrophages. Importantly, it was recently shown that DDX3 directly regulates the translation of p38 MAPK, Rac1, STAT1 (TGFβ) and TAK1, which play essential roles in NF-κB regulation (38). The direct role of DDX3 in regulating pro-inflammatory responses in the pathogenesis of bowel disease and Listeria infection were also recently observed (62,63).…”
Section: Discussionmentioning
confidence: 96%
“…The RNA helicase activity of DDX3 is needed for the efficient translation of certain mRNAs with highly structured 5'-UTR (Guenther et al, 2018;Sen et al, 2015). A known direct target of DDX3 in mammals is RAC1 (Chen et al, 2015;Chen et al, 2016;Ku et al, 2018), which is extremely conserved throughout vertebrate evolution (100% identical between human and X. tropicalis orthologs). Interestingly, mutations in RAC1 cause craniofacial disorders and other potential NC and CNS defects, which are highly similar to those caused by DDX3X mutations (Reijnders et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…can promote translational initiation of mRNAs with long and structured 5'-UTR through its RNA helicase activity, a function that is conserved from yeast to humans (Guenther et al, 2018;Sen et al, 2015). One of these mRNAs encodes RAC1, which can mediate DDX3 function in other physiological processes in mammals (Chen et al, 2015;Chen et al, 2016;Ku et al, 2018). Notably, RAC1 can activate AKT through its downstream effector p21-activated kinase (PAK) (Higuchi et al, 2008).…”
Section: Rac1 Is Likely An Immediate Downstream Effector Of Ddx3 In Nmentioning
confidence: 99%